Associations of chronotype with social jetlag and behavioral problems in preschool children. (14th September 2015) - Doi, Yuriko; Ishihara, Kaneyoshi; Uchiyama, Makoto
Abstract : The timing, duration, and intensity of sleep are determined by the interaction between a sleep-wake-dependent homeostatic process and a sleep-wake-independent, intrinsic, clock-like circadian process. Chronotype represents individual differences in diurnal preferences, which are not only genetically determined but also influenced by social and environmental factors. Thus, the discrepancy between biological and social clocks, so-called "social jetlag", occurs. Chronotype, social jetlag, and the links between chronotype and behavioral problems are well documented in adults and adolescents. However, such studies on young children are limited. We conducted a survey of sleep and health for preschool children attending kindergarten or childcare centers in Wako, Okayama and Kurashiki cities, Japan, between May and July 2012. A total of 654 children aged 4–6 years (342 boys and 312 girls, with an average age of 4.7 years) were assessed using the Children's ChronoType Questionnaire and the Strength and Difficulties Questionnaire. Morning (M)-type, neither (N)-type and evening (E)-type accounted for 36.2%, 54.0% and 9.8% of the participants, respectively. The weekday-to-weekend differences in midsleep time – originally proposed as the concept of social jetlag – were 11, 25 and 35 min for M-, N- and E-types, respectively. There was a negative correlation between chronotype and sleep period during weekdays ( p  < 0.001) and a positive correlation on weekends ( p  < 0.001). The weekday-to-weekend difference in sleep period was 0.5 h for E-types, whereas there was no difference for M-types. Binomial logistic regression analyses were used to examine the links between chronotype and behavioral problems, adjusted for participants' sex, age, childcare programs and locations. Chronotype was significantly associated with hyperactivity/inattention: N-type (adjusted OR = 1.74, 95% CI = 1.03–2.95, p  < 0.05) and E-type (adjusted OR = 2.47, 95% CI = 1.18–5.20, p  < 0.05). E-type was significantly associated with conduct problems (adjusted OR = 2.11, 95% CI = 1.03–4.31, p  < 0.05) and peer problems (adjusted OR = 2.75, 95% CI = 1.18–6.44, p  < 0.05). The results suggest that E-type children are vulnerable to higher social jetlag and more behavioral problems. The immature adjustment function of their endogenous circadian pacemakers may not be able to correct a small but significant social jetlag to synchronize with their social clocks. Furthermore, guidance based on chronobiological evidence is required for parents, teachers and health professionals to help children achieve optimal sleep and reduce behavioral problems.